Examining the Implementation of the National Protocol for Sexual Assault Medical Forensic Examinations. Issue 2 (16th April 2022) - Langness, Mel; Zweig, Janine M.; Tiry, Emily; Henderson, Erica; Stahlmann, Nicole; Bastomski, Sara
ABSTRACT: The National Protocol for Sexual Assault Medical Forensic Examinations, Adult/Adolescent, 2nd edition, or SAFE Protocol, is a voluntary guide that assists local and state jurisdictions with their responses to sexual assault by institutionalizing best practices around survivor care and evidence collection, particularly for sexual assault nurse examiners (SANEs) completing medical forensic examinations. We examined the uptake of the SAFE Protocol in communities across the United States by analyzing data from a set of national surveys of forensic nursing programs and victim advocates within the same communities. We studied four implementation outcomes: the acceptability, adoption, reach, and sustainability of the SAFE Protocol. SANEs and advocates reported that stakeholders responding to sexual assault—including forensic nurses, advocates, law enforcement, and prosecutors—have high implementation of the Protocol, which indicates how important individual stakeholder engagement is in actively facilitating the adoption of it. However, when information from SANEs and advocates from the same community are compared, the extent to which the SAFE Protocol is reported to be implemented with fidelity across U.S. jurisdictions is mixed.